Preparation method of zinc negative electrode of hydrophobic and zinc-loving sulfydryl functionalized zinc ion energy storage device

By performing hydrophobic and zinc-philic thiol functionalization of zinc anode of zinc ion energy storage devices, the problems of dendrites growth, hydrogen evolution reaction and anode corrosion are solved, and the electrochemical performance and cyclic stability of zinc ion batteries are significantly improved.

CN119447155APending Publication Date: 2025-02-14NANJING UNIV OF AERONAUTICS & ASTRONAUTICS
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411722886.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Commercially used metal zinc is prone to dendrite growth, hydrogen evolution reaction and anode corrosion during the zinc ion battery cycle, resulting in poor cycling stability, low reversibility and shortened life of the device.

Method used

The zinc negative electrode of zinc ion energy storage device is surface modified by hydrophobic and zinc-philic thiol functional treatment method. The specific method is to dissolve the thiol-containing organic acid and a nonionic surfactant in an organic solvent and soak the zinc foil to form a zinc-thiol organic acid coordination compound layer with a micro-nano structure.

Benefits of technology

By forming a hydrophobic and zinc-philic interface layer, the hydrolysis reaction on the negative electrode side is effectively hindered, the uniform deposition of zinc ions is guided, dendrites are inhibited, and the electrochemical performance and cyclic stability of zinc ion batteries are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447155A_ABST
    Figure CN119447155A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a zinc negative electrode of a hydrophobic and zinc-loving sulfydryl functionalized zinc ion energy storage device, and belongs to the technical field of new energy materials and electrochemistry. The preparation method comprises the following steps: dissolving organic acid with sulfydryl and a nonionic surfactant in an organic solvent to obtain a solution A; zinc is soaked in the solution A for surface modification treatment, and the negative electrode material for the zinc ion energy storage device is obtained. According to the invention, the mercapto organic acid is used as a ligand, Zn is used as a central metal, the zinc ligand micro-nano array of the mercapto organic acid is grown on the surface of the zinc foil, the zinc ligand micro-nano array has a hydrophobic effect, and in addition, a mercapto group on the organic ligand is a zinc-loving group. The hydrophobic zinc-loving structure on the surface of the zinc foil can effectively hinder hydrolysis reaction on the negative electrode side and guide uniform deposition of zinc ions, so that Zn dendritic crystals are effectively inhibited.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of new energy materials and electrochemical technology, and in particular to a method for preparing a zinc negative electrode of a zinc ion energy storage device treated with hydrophobic and zinc-philic thiol functionalization. Background Art

[0002] Rechargeable aqueous zinc-ion energy storage devices with zinc metal anodes have high specific capacity (820 mAh g -1 and 5855mAh cm -2 ), suitable reduction potential (-0.76V relative to the standard hydrogen electrode), safe, non-toxic and non-flammable electrolyte, low cost, environmental friendliness and abundant zinc raw materials, it has attracted much attention as a promising solution for clean electrochemical energy storage. Despite these advantages, zinc anodes are still subject to problems such as dendrite growth, hydrogen evolution reaction and anode corrosion in actual use. Due to the uneven surface of commercial metallic zinc, dendrite growth and uneven nucleation are more likely to occur during the cycling of zinc-ion batteries, ultimately resulting in poor device cycling stability, low reversibility and shortened life.

[0003] In order to improve the stability and electrochemical performance of zinc metal anode, the current development strategies are generally studied from the aspects of electrode structure design, electrode surface modification, electrolyte modification, and diaphragm design. Compared with other strategies, electrode surface modification is favored by researchers because it is efficient and convenient, and can effectively regulate the growth of zinc and reduce the occurrence of side reactions. Summary of the invention

[0004] Based on the above content, the purpose of the present invention is to provide a method for preparing a zinc negative electrode of a zinc ion energy storage device with a hydrophobic and zinc-philic thiol functionalized treatment.

[0005] In order to achieve the above object, the present invention provides the following technical solutions:

[0006] One of the technical solutions of the present invention is a method for preparing a negative electrode material for a zinc ion energy storage device, which comprises dissolving an organic acid with a mercapto group and a non-ionic surfactant in an organic solvent to obtain a solution A; and then immersing zinc in the solution A for surface modification treatment.

[0007] The second technical solution of the present invention is a negative electrode material for a zinc ion energy storage device prepared by the above preparation method.

[0008] The third technical solution of the present invention is a zinc ion energy storage device, the raw materials of which include the negative electrode material for the zinc ion energy storage device mentioned above.

[0009] A fourth technical solution of the present invention is a method for inhibiting the growth of zinc surface dendrites, comprising performing surface modification treatment on zinc using the preparation method described in the above technical solution.

[0010] The present invention discloses the following technical effects:

[0011] (1) The preparation method of the present invention has a simple process, a short preparation cycle, and is suitable for large-scale surface treatment of zinc foil.

[0012] (2) The present invention uses mercapto organic acid as a ligand and Zn as a central metal to grow a micro-nano array of zinc ligands of mercapto organic acid on the surface of zinc foil, which has a hydrophobic effect. In addition, the mercapto group on the organic ligand is a zinc-philic group. The hydrophobic zinc-philic structure on the surface of the zinc foil can effectively hinder the hydrolysis reaction on the negative electrode side and guide the uniform deposition of zinc ions, thereby effectively inhibiting Zn dendrites. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0014] Figure 1 The SEM images of the untreated zinc foil and the zinc foil obtained in Example 1 and the EDS images of the treated zinc foil, wherein a is the SEM image of the untreated zinc foil, b is the SEM image of the zinc foil obtained in Example 1, and c, d, e, and f are the EDS images of O, C, S, and Zn of the zinc foil obtained in Example 1, respectively;

[0015] Figure 2 The zinc foil obtained by untreated zinc foil and Example 1 was assembled into a zinc ion capacitor at 1A g -1 SEM images after 100 cycles of current density, where a is the untreated zinc foil and b is the zinc foil obtained in Example 1;

[0016] Figure 3 These are SEM images of the untreated zinc foil and the zinc foil obtained in Example 1 after being immersed in an acidic electrolyte for one week, wherein a is the untreated zinc foil and b is the zinc foil obtained in Example 1;

[0017] Figure 4 FT-IR spectrum of the zinc foil obtained in Example 1;

[0018] Figure 5 XRD spectra of untreated zinc foil and zinc foil obtained in Example 1;

[0019] Figure 6 The zinc foil obtained in Example 1 was untreated and the zinc foil was treated with 2 mol L -1Contact angle of ZnSO4 solution;

[0020] Figure 7 The long cycle performance diagram of zinc ion capacitor assembled with untreated zinc foil;

[0021] Figure 8 This is a long cycle performance diagram of a zinc ion capacitor assembled with the zinc foil obtained in Example 1;

[0022] Fig. 9 Symmetrical battery cycle performance test of untreated zinc foil and zinc foil obtained in Example 1;

[0023] Fig.10 (a) Tafel test graph, (b) LSV test graph of untreated zinc foil, PMAA-treated zinc foil in Comparative Example 1, and MBA-treated zinc foil in Example 1;

[0024] Fig.11 It is a comparison diagram of the zinc foil obtained in Example 1 and Comparative Example 2, wherein a is Example 1 and b is Comparative Example 2;

[0025] Fig.12 This is a microscopic schematic diagram of the zinc foil obtained in Comparative Example 2. DETAILED DESCRIPTION

[0026] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0027] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0028] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0029] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0030] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0031] The requirements for surface modification of zinc are similar to the construction of solid electrolyte interface (SEI), and the requirements for microstructure and zinc affinity are very high. The present invention treats zinc foil with an organic acid with a mercapto group. Since the organic acid contains a mercapto group, the mercapto group and the carboxyl group simultaneously remove a hydrogen and connect to the same zinc ion during the reaction to form a ligand, thereby constructing a layer of hydrophobic and zinc-affinity artificial interface layer (SEI) on the surface of the zinc foil to improve the performance of the zinc ion energy storage device. The interface surface can produce a layer of hydrophobic zinc ligands with mercapto organic acid, the reaction corrosion resistance is improved, and the crystal plane is changed, so that the (002) crystal plane is more exposed, thereby improving the interface nucleation, making the zinc ions uniformly deposited, the polarization voltage is reduced, and the generation of zinc dendrites is inhibited, and finally the electrochemical performance of the zinc ion battery is improved.

[0032] Specifically, the first aspect of the present invention provides a method for preparing a negative electrode material for a zinc ion energy storage device, wherein an organic acid with a mercapto group and a non-ionic surfactant are dissolved in an organic solvent to obtain a solution A; and then zinc is immersed in the solution A for surface modification.

[0033] In some embodiments of the present invention, the organic acid with a thiol group is 2-mercaptobenzoic acid, 3-mercaptobenzoic acid, 4-mercaptobenzoic acid or 4-mercaptophenylacetic acid; the concentration of the organic acid with a thiol group in the solution A is 0.01-0.2 mol / L, preferably 0.01-0.05 mol / L.

[0034] In some embodiments of the present invention, the non-ionic surfactant is polyvinylpyrrolidone K30 (PVP); the concentration of the non-ionic surfactant in the solution A is 1-10 g / L, preferably 4-6 g / L.

[0035] The invention firstly soaks zinc in a mixed solution of an organic acid with a mercapto group and a nonionic surfactant, and after reaction, a coordination compound layer of zinc-mercapto organic acid with a micro-nano structure is formed on the surface of the zinc. The zinc foil obtained by treating with a specific mixed solution of an organic acid with a mercapto group and a surfactant has good performance, can resist corrosion of the electrolyte, effectively inhibit zinc dendrites, and stabilize the electrode / electrolyte interface.

[0036] In the present invention, the addition of surfactant can promote the reaction rate and enable the ligand to be formed uniformly on the surface of zinc foil. If the addition of surfactant is omitted, on the one hand, the reaction rate will be very slow and the reaction time will be too long, and on the other hand, the reaction will be uneven, thereby causing the performance of the zinc negative electrode to decrease instead of increase.

[0037] The right amount of acid and the right amount of surfactant can control the reaction rate within a suitable range so that the modified layer obtained after the reaction is more uniform, can better induce the parallel growth of Zn, avoid the tip effect, and better inhibit the formation of dendrites. Therefore, the present invention preferably has the concentration of the organic acid with a thiol group and the non-ionic surfactant within the above parameter range.

[0038] In the present invention, the organic solvent may be one that can fully dissolve the organic acid with a mercapto group and the nonionic surfactant, such as methanol.

[0039] In some embodiments of the present invention, before immersing zinc in the solution A for surface modification, a step of pre-treating the zinc is also included; the pre-treatment specifically includes: polishing the zinc surface to remove the oxide layer and oil stains and then cleaning.

[0040] In some embodiments of the present invention, the soaking time is 1-4 hours.

[0041] In some embodiments of the present invention, when zinc is immersed in the solution A for surface modification treatment, the temperature of the solution A is 20-45°C.

[0042] In some embodiments of the present invention, after the surface modification treatment, the method further includes drying the zinc after the surface modification treatment; the drying environment is a vacuum environment, the drying temperature is 60 to 100° C., and the drying time is 1 to 3 hours.

[0043] A second aspect of the present invention provides a negative electrode material for a zinc ion energy storage device prepared by the above preparation method.

[0044] A third aspect of the present invention provides a zinc ion energy storage device, the raw materials of which include the negative electrode material for the zinc ion energy storage device.

[0045] A fourth aspect of the present invention provides a method for inhibiting the growth of zinc surface dendrites, wherein the surface of zinc is modified using the preparation method described in the above technical solution.

[0046] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.

[0047] The test reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the experimental methods described, unless otherwise specified, are all conventional methods.

[0048] Example 1

[0049] Step 1: Grind the zinc foil with sandpaper and cut it into discs with a diameter of 12 mm. Use anhydrous ethanol to ultrasonically clean it for 10 minutes each time for three times, which is conducive to removing the passivation layer and oil stains on the surface of the zinc foil.

[0050] Step 2: Add 20 ml of methanol into a beaker, then add 0.0308 g of 2-mercaptobenzoic acid and 0.1 g of polyvinylpyrrolidone K30, and stir at room temperature for 20 min to obtain a uniform mixed solution;

[0051] Step 3: Place the treated zinc foil into the mixed solution and soak it at room temperature for 4 hours;

[0052] Step 4: Wash the zinc foil soaked in the mixed solution with methanol three times, and then put it into a vacuum drying oven at 60° C. for 6 hours to obtain the zinc foil after surface modification.

[0053] Example 2

[0054] Step 1: Grind the zinc foil with sandpaper and cut it into discs with a diameter of 12 mm. Use anhydrous ethanol to ultrasonically clean it for 10 minutes each time for three times, which is conducive to removing the passivation layer and oil stains on the surface of the zinc foil.

[0055] Step 2: Add 20 ml of methanol into a beaker, then add 0.0308 g of 3-mercaptobenzoic acid and 0.1 g of polyvinyl pyrrolidone, and stir at room temperature for 20 min to obtain a uniform mixed solution;

[0056] Step 3: Place the treated zinc foil into the mixed solution and soak it at room temperature for 3 hours;

[0057] Step 4: Wash the zinc foil soaked in the mixed solution with methanol three times, and then put it into a vacuum drying oven at 60° C. for 6 hours to obtain the zinc foil after surface modification.

[0058] Example 3

[0059] Step 1: Grind the zinc foil with sandpaper and cut it into discs with a diameter of 12 mm. Use anhydrous ethanol to ultrasonically clean it for 10 minutes each time for three times, which is conducive to removing the passivation layer and oil stains on the surface of the zinc foil.

[0060] Step 2: Add 20 ml of methanol into a beaker, then add 0.0336 g of 4-mercaptophenylacetic acid and 0.1 g of polyvinyl pyrrolidone, and stir at room temperature for 20 min to obtain a uniform mixed solution;

[0061] Step 3: Place the treated zinc foil into the mixed solution and soak it at room temperature for 4 hours;

[0062] Step 4: Wash the zinc foil soaked in the mixed solution with methanol three times, and then put it into a vacuum drying oven at 60° C. for 6 hours to obtain the zinc foil after surface modification.

[0063] Comparative Example 1

[0064] Step 1: Grind the zinc foil with sandpaper and cut it into discs with a diameter of 12 mm. Use anhydrous ethanol to ultrasonically clean it for 10 minutes each time for three times, which is conducive to removing the passivation layer and oil stains on the surface of the zinc foil.

[0065] Step 2: Dissolve 5 mL of methacrylic acid (PMAA) in 75 mL of dimethyl sulfoxide, stir evenly, and then apply it to the treated zinc foil surface by scraping. After standing for 12 hours, the surface-modified zinc foil is obtained.

[0066] Comparative Example 2

[0067] Step 1: Grind the zinc foil with sandpaper and cut it into discs with a diameter of 12 mm. Use anhydrous ethanol to ultrasonically clean it for 10 minutes each time for three times, which is conducive to removing the passivation layer and oil stains on the surface of the zinc foil.

[0068] Step 2: Add 20 ml of methanol and 0.0308 g of 2-mercaptobenzoic acid into a beaker, and stir at room temperature for 20 min to obtain a uniform mixed solution;

[0069] Step 3: Place the treated zinc foil into the mixed solution and soak it at room temperature for 4 hours;

[0070] Step 4: Wash the zinc foil soaked in the mixed solution with methanol three times, and then dry it in a vacuum drying oven at 60° C. for 6 hours to obtain a zinc foil after surface modification (the difference from Example 1 is that the addition of polyvinyl pyrrolidone K30 is omitted).

[0071] Effect verification

[0072] 1. The untreated zinc foil and the zinc foil obtained in Example 1 were subjected to microstructural characterization using a scanning electron microscope. Figure 1 As shown in the figure, a is an untreated zinc foil with many scratches on its surface; b is a zinc foil treated in Example 1, which can be seen to have a multi-layer sphere with a micron structure. This is the organic ligand formed by 2-mercaptobenzoic acid on the surface of the zinc foil. The micro-nano structure formed can provide hydrophobic properties for the zinc foil. In addition, EDS test shows that there are elements such as O, C, S, and Zn on the surface of the zinc foil. The mercapto group has a strong adsorption effect on zinc ions, which is conducive to promoting the uniform nucleation and deposition of the Zn metal electrode.

[0073] 2. The untreated zinc foil and the zinc foil obtained in Example 1 were assembled into a battery and cycled for 100 cycles; Figure 2 As shown, Figure a is the SEM surface of the untreated zinc foil after 100 cycles, and Figure b is the SEM surface of the zinc foil treated in Example 1 after 100 cycles. It can be seen that the surface dendrites of the untreated zinc foil are serious after 100 cycles, while only smaller dendrites exist on the surface of the treated zinc foil. It can be seen that the zinc foil treated with 2-mercaptobenzoic acid has a significant effect of inhibiting dendrites.

[0074] 3. The untreated zinc foil and the zinc foil obtained in Example 1 were immersed in 2M ZnSO4 electrolyte for one week; Figure 3 As shown, Figure a is the SEM surface of the untreated zinc foil after being immersed in the acidic electrolyte for one week, and Figure b is the SEM surface of the zinc foil treated in Example 1 after being immersed in the acidic electrolyte for one week. It can be seen that there are many flaky dendrites on the surface of the untreated zinc foil in Figure a, while the surface of Figure b is relatively clean with fewer by-products; this shows that the Zn-MBA layer on the surface of the zinc foil can protect the zinc anode from electrolyte corrosion and reduce side reactions.

[0075] 4. The zinc foil treated in Example 1 was subjected to FT-IR testing. It can be seen that there are a large number of S-Zn bonds in the zinc foil surface complex, which clearly shows that 2-mercaptobenzoic acid can form a zinc ligand ( Figure 4 ).

[0076] 5. By comparing the XRD spectra of the untreated zinc foil and the zinc foil obtained in Example 1, it can be seen that the crystal planes on the zinc foil surface except (002) are reduced after the reaction ( Figure 5 , in the figure, Zn-MBA@Zn represents the zinc foil obtained in Example 1, and bare Zn represents the untreated zinc foil).

[0077] 6. The untreated zinc foil and the zinc foil obtained in Example 1 were subjected to 2 mol L -1 The contact angle experiment of ZnSO4 solution, such as Figure 6 As shown (in the figure, Zn-MBA@Zn represents the zinc foil obtained in Example 1, and bare Zn represents the untreated zinc foil), the contact angle of the zinc foil obtained in Example 1 is larger than those of the untreated zinc foil and Comparative Example 1, which indicates that the treated zinc foil has a certain hydrophobicity.

[0078] 7. The zinc foil obtained in Example 1 and the untreated zinc foil were assembled into zinc ion capacitors and tested at a current density of 1 mAg -1 The long cycle performance at a current density of Figure 7 , 8It can be seen that the treated zinc foil can be stably cycled for 17,000 cycles and maintain an average CE of 99.9%. The battery assembled with the zinc foil obtained in Example 1 exhibits good electrochemical performance.

[0079] 8. The zinc foil obtained in Example 1 and the untreated blank zinc foil were assembled into Zn / / Zn symmetrical cells and tested at 1 mA cm -2 The current density and 1 mAh cm -2 The capacity-limited cycling stability is given by Fig. 9 It can be seen (in the figure, Zn-MBA@Zn represents the zinc foil obtained in Example 1, and bare Zn represents the untreated zinc foil) that the battery assembled with the zinc foil obtained in Example 1 maintained stability for 550 hours without any obvious overpotential increase, and this stability exceeded that of the untreated blank zinc foil, indicating that the hydrophobic zinc-philic interface on the zinc foil surface effectively inhibited side reactions, prolonged the cycle durability, and reduced voltage hysteresis.

[0080] 9. The zinc foil obtained in Example 1 and the zinc foil obtained in Comparative Example 1 were subjected to Tafel, LSV, and symmetric battery long cycle tests ( Fig.10 In the figure, bare Zn represents untreated zinc foil, Zn-MBA@Zn represents zinc foil obtained in Example 1, and Zn-PMAA@Zn represents zinc foil obtained in Comparative Example 1). It can be seen that compared with untreated zinc foil, the zinc foil treated with organic carboxylic acid methacrylic acid has improved corrosion resistance and inhibition of hydrogen evolution, but it is difficult to achieve the technical effect of the present invention. This is because the spontaneous reaction between the zinc negative electrode and the organic carboxylic acid to generate the SEI film in situ is only a reaction between the carboxyl group and the zinc ion, and the organic acid used in the present invention contains a thiol group. During the reaction, the thiol group and the carboxyl group simultaneously remove a hydrogen and are connected to the same zinc ion to form a ligand.

[0081] 10. Fig.11 This is a comparison diagram of the zinc foil treated in Example 1 and the zinc foil treated in Comparative Example 2. Fig.12 This is a microscopic diagram of the zinc foil treated in Comparative Example 2. It can be seen that the surface of the zinc foil reacts unevenly without adding a surfactant.

[0082] The present invention carried out the same effect verification test as in Example 1 on the zinc foil prepared in Example 2 and Example 3. The test results were similar to those in Example 1. The zinc foil treated with 3-mercaptobenzoic acid and 4-mercaptophenylacetic acid had a significant effect of inhibiting dendrites, and was able to protect the zinc anode from electrolyte corrosion and reduce side reactions. After being assembled into a battery, it showed good electrochemical performance.

[0083] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a negative electrode material for a zinc ion energy storage device, characterized in that: An organic acid with a mercapto group and a nonionic surfactant are dissolved in an organic solvent to obtain a solution A; then zinc is immersed in the solution A for surface modification treatment.

2. The method for preparing a negative electrode material for a zinc ion energy storage device according to claim 1, wherein: The organic acid with a thiol group is 2-mercaptobenzoic acid, 3-mercaptobenzoic acid, 4-mercaptobenzoic acid or 4-mercaptophenylacetic acid; and the concentration of the organic acid with a thiol group in the solution A is 0.01-0.2 mol / L.

3. The method for preparing a negative electrode material for a zinc ion energy storage device according to claim 1, wherein: The non-ionic surfactant is polyvinyl pyrrolidone K30; the concentration of the non-ionic surfactant in the solution A is 1-10 g / L.

4. The method for preparing a negative electrode material for a zinc ion energy storage device according to claim 1, wherein: The soaking time is 1-4h.

5. The method for preparing the negative electrode material for zinc ion energy storage device according to claim 1, characterized in that: After the surface modification treatment is completed, the method further includes drying the zinc after the surface modification treatment; the drying environment is a vacuum environment, the drying temperature is 60 to 100° C., and the drying time is 1 to 3 hours.

6. A negative electrode material for a zinc ion energy storage device prepared by the preparation method according to any one of claims 1 to 5.

7. A zinc ion energy storage device, characterized in that: The raw materials include the negative electrode material for the zinc ion energy storage device according to claim 6.

8. A method for inhibiting zinc surface dendrite growth, characterized in that: The surface of zinc is modified by the preparation method described in any one of claims 1 to 5.

Citation Information

Patent Citations

  • Preparation method and application of multifunctional zinc negative electrode protection layercapable of growing rapidly in situ

    CN113363410A

  • Preparation method and application of nano zinc sulfide with adjustable crystal structure

    CN118811856A

  • Zinc negative electrode, preparation method thereof and zinc-air battery

    CN118983390A